Vibro-acoustic analysis of composite circular disc with various orthotropic properties under thermal environment. (27th August 2008) - Rajesh Kumar, Boorle; Ganesan, N.; Sethuraman, Raju
Composite circular discs with polar orthotropic and rectangular orthotropic fibres of different composite materials are modelled and their vibration response due to harmonic point load under thermal environment was computed by Finite Element Method (FEM) using ANSYS. Acoustic response of composite circular disc was computed by coupling the vibration data from FEM to the Boundary Element Method (BEM) using LMS SYSNOISE.